ICT lessons for single mothers and orphans - UMP, PNC
Universiti Malaysia Pahang (UMP) continued to contribute its expertise in developing the community’s socio-economic and making it relevant to the people as reflected in a recent ICT workshop held for 311 single mothers and orphans in the state.